P-MAPA and IL-12 Differentially Regulate Proteins Associated with Ovarian Cancer Progression: A Proteomic Study - Júnior, Luiz Antonio Lupi; Cucielo, Maira Smaniotto; Domeniconi, Raquel Fantin; Dos Santos, Lucilene Delazari [UNESP]; Silveira, Henrique Spaulonci; Da Silva Nunes, Iseu; Martinez, Marcelo; Martinez, Francisco Eduardo; Fávaro, Wagner José; Chuffa, Luiz Gustavo De Almeida (American Chemical Society (ACS), 2019)
To investigate the potential role of immunotherapies in the cellular and molecular mechanisms associated with ovarian cancer (OC), we applied a comparative proteomic toll using protein identification combined with mass spectrometry. Herein, the effects of the protein aggregate magnesium-ammonium phospholinoleate-palmitoleate anhydride, known as P-MAPA, and the human recombinant interleukin-12 (hrIL-12) were tested alone or in combination in human SKOV-3 cells. The doses and period were defined based on a previous study, which showed that 25 μg/mL P-MAPA and 1 ng/mL IL-12 are sufficient to reduce cell metabolism after 48 h. Indeed, among 2,881 proteins modulated by the treatments, 532 of them were strictly concordant and common. P-MAPA therapy upregulated proteins involved in tight junction, focal adhesion, ribosome constitution, GTP hydrolysis, semaphorin interactions, and expression of SLIT and ROBO, whereas it downregulated ERBB4 signaling, toll-like receptor signaling, regulation of NOTCH 4, and the ubiquitin proteasome pathway. In addition, IL-12 therapy led to upregulation of leukocyte migration, tight junction, and cell signaling, while cell communication, cell metabolism, and Wnt signaling were significantly downregulated in OC cells. A clear majority of proteins that were overexpressed by the combination of P-MAPA with IL-12 are involved in tight junction, focal adhesion, DNA methylation, metabolism of RNA, and ribosomal function; only a small number of downregulated proteins were involved in cell signaling, energy and mitochondrial processes, cell oxidation and senescence, and Wnt signaling. These findings suggest that P-MAPA and IL-12 efficiently regulated important proteins associated with OC progression; these altered proteins may represent potential targets for OC treatment in addition to its immunoadjuvant effects.